A double-layer hollow core-shell structure porous carbon hybrid material and its preparation method and application

By adopting the preparation method of porous carbon hybrid material with double-layer hollow core-shell structure, the shortcomings of existing porous carbon materials in taking into account high specific surface area, structural stability and efficient ion transport are solved, and the electrochemical performance of sodium ion batteries is significantly improved.

CN116040607BActive Publication Date: 2025-03-07HEFEI UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310056667.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-17
Publication Date
2025-03-07
Estimated Expiration
2043-01-17

AI Technical Summary

Technical Problem

The existing single porous carbon materials are difficult to take into account high specific surface area, structural stability and efficient ion transport, which limits their electrochemical performance in the fields of sodium ion batteries.

Method used

The preparation method of porous carbon hybrid material with double-layer hollow core-shell structure is adopted. By combining Co-MOF-74 with ZIF-8, a double-layer hollow core-shell structure is formed, which is converted into porous carbon after annealing by argon protection, enhancing its specific surface area and structural stability.

Benefits of technology

The high specific surface area, structural stability and rapid ion transport of porous carbon hybrid materials with double-layer hollow core-shell structure are achieved, which significantly improves the cycle stability and rate performance of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116040607B_ABST
    Figure CN116040607B_ABST
Patent Text Reader

Abstract

The invention discloses a double-layer hollow core-shell structure porous carbon hybrid material and its preparation method and application, the method comprising the following steps: 2-methylimidazole powder is dissolved in methanol, double-layer hollow Co-MOF-74 powder is added to form a uniform suspension A; zinc nitrate hexahydrate is dissolved in methanol to form solution B; solution B is added to suspension A, centrifuged, washed, and dried to obtain a double-layer hollow Co-MOF-74@ZIF-8 core-shell structure powder; double-layer hollow Co-MOF-74@ZIF-8 core-shell structure powder is annealed under argon protection to obtain a double-layer hollow core-shell structure porous carbon hybrid material, placed in a nitric acid solution, stirred in a water bath and reacted, the product is centrifuged, then washed clean with ethanol, and dried to obtain a pure double-layer hollow core-shell structure porous carbon hybrid material. The present invention gives full play to the advantages of two MOF material-derived porous carbons, and has both the conductivity of graphitized carbon and the high specific surface area of ​​porous carbon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of synthesis of micro-nano composite materials, and in particular to a double-layer hollow core-shell structure porous carbon hybrid material and a preparation method and application thereof. Background Art

[0002] Metal-organic frameworks (MOFs) are crystalline metal-organic hybrid compounds composed of metal ions and organic ligands. These materials have some advantages, such as high specific surface area, adjustable structure and composition, and uniform pore size. MOFs-derived materials have been widely used in catalysis, gas separation, energy storage and other fields. However, each porous carbon derived from a single MOF often cannot combine all the required properties, thus giving a discount on the comprehensive performance. Summary of the invention

[0003] The purpose of the present invention is to provide a double-layer hollow core-shell structure porous carbon hybrid material and its preparation method and application. The material preparation method is simple, low in cost and has broad application prospects.

[0004] In one aspect of the present invention, the present invention provides a method for preparing a double-layer hollow core-shell structure porous carbon hybrid material. According to an embodiment of the present invention, the method comprises the following steps:

[0005] (1) 2-methylimidazole powder was dissolved in methanol, and then double-layer hollow Co-MOF-74 powder was added to form a uniform suspension A, which was stirred at room temperature;

[0006] (2) dissolving zinc nitrate hexahydrate in methanol to form solution B;

[0007] (3) Slowly adding solution B to suspension A, stirring continuously at room temperature, centrifuging the product, washing with ethanol, and drying in an oven to obtain a double-layer hollow Co-MOF-74@ZIF-8 core-shell structure powder;

[0008] (4) The double-layer hollow Co-MOF-74@ZIF-8 core-shell structure powder was annealed under argon protection to obtain a double-layer hollow core-shell structure porous carbon hybrid material;

[0009] (5) The double-layer hollow core-shell structure porous carbon hybrid material is placed in a nitric acid solution, stirred in a water bath for reaction, and then the product is centrifuged and separated, and then washed with ethanol, and dried in an oven to obtain a pure double-layer hollow core-shell structure porous carbon hybrid material.

[0010] In addition, the method for preparing a double-layer hollow core-shell structured porous carbon hybrid material according to the above embodiment of the present invention may also have the following additional technical features:

[0011] In some embodiments of the present invention, in step S1, the method for preparing double-layer hollow Co-MOF-74 powder comprises the following steps:

[0012] S101, adding 2,5-dihydroxyterephthalic acid and ZIF-67 to N,N-dimethylformamide to form a solution by ultrasonication, then transferring the solution into a high-pressure reactor and placing it in an oven for reaction;

[0013] S102, centrifugally separating the product obtained in step S101, washing it with ethanol, and drying it in an oven to obtain a double-layer hollow Co-MOF-74 powder.

[0014] In some embodiments of the present invention, in the step S101, the mass ratio of 2,5-dihydroxyterephthalic acid to ZIF-67 is 1:1, the ultrasonic time is 0-30 min, the oven temperature is 80-150° C., and the reaction time is 30-1440 min; in the step S102, the oven temperature is 25-100° C., and the drying time is 30-720 min.

[0015] In some embodiments of the present invention, in the step S1, the concentration of 2-methylimidazole in the suspension A is 0.1-2 mol / L, the concentration of the double-layer hollow Co-MOF-74 is 1-5 g / L, and the room temperature is 25°C; in the step S2, the concentration of the solution B is 0.1-1 mol / L; in the step S3, the room temperature is 25°C, the stirring time is 1-60 min, the temperature of the oven is 25-85°C, and the drying time is 30-720 min; in the step S4, the annealing temperature is 600-900°C, and the insulation time is 1-10 h; in the step S5, the volume ratio of concentrated nitric acid to water in the nitric acid solution is 1:2, the water bath temperature is 25-90°C, the water bath time is 0.5-48 h, the oven temperature is 25-100°C, and the drying time is 30-720 min.

[0016] In another aspect of the present invention, the present invention provides a double-layer hollow core-shell structure porous carbon hybrid material prepared by the preparation method of the double-layer hollow core-shell structure porous carbon hybrid material.

[0017] In another aspect of the present invention, the present invention provides a negative electrode material for a sodium ion battery. In an embodiment of the present invention, the negative electrode material is prepared using a double-layer hollow core-shell structure porous carbon hybrid material.

[0018] In another aspect of the present invention, the present invention provides a method for preparing a negative electrode material for a sodium ion battery. In an embodiment of the present invention, the method comprises the following steps:

[0019] S1, uniformly mixing the double-layer hollow core-shell structure porous carbon hybrid material, conductive carbon black and polyvinylidene fluoride, dissolving them in 1-methyl-2-pyrrolidone to prepare a slurry, then uniformly coating the slurry on a copper foil current collector, and drying the slurry in a vacuum drying oven;

[0020] S2. Slice the dried copper foil current collector to make negative electrode materials for sodium ion batteries.

[0021] In addition, the method for preparing a sodium ion battery according to the above embodiment of the present invention may also have the following additional technical features:

[0022] In some embodiments of the present invention, in step S1, the double-layer hollow core-shell structure porous carbon hybrid material, conductive carbon black, and polyvinylidene fluoride are in a mass ratio of 8:1:1, 1-methyl-2-pyrrolidone is 350 μl, the drying temperature is 25-100° C., and the drying time is 30-720 min.

[0023] In another aspect of the present invention, the present invention provides a method for preparing a sodium ion battery. In an embodiment of the present invention, the method comprises the following steps:

[0024] The negative electrode material of the sodium ion battery is used as a working electrode, the glass fiber is used as a diaphragm, and the electrolyte is a binary electrolyte. The assembly is performed in a glove box filled with argon gas to obtain the sodium ion battery.

[0025] In addition, the method for preparing a sodium ion battery according to the above embodiment of the present invention may also have the following additional technical features:

[0026] In some embodiments of the present invention, the electrolyte is sodium trifluoromethanesulfonate, the size of the working electrode is 12 mm, and the positive electrode material of the sodium ion battery is a metallic sodium sheet.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1) The double-layer hollow core-shell structure porous carbon hybrid material prepared by the present invention, the derived carbon material is a double-layer hollow core-shell structure, has a large specific surface area, strong structural stability, and a fast ion transfer rate, thereby effectively improving the electrochemical properties of sodium ion batteries, such as cycle stability and rate performance.

[0029] 2) The double-layer hollow core-shell structure porous carbon hybrid material prepared by the present invention has porous carbon on the outside with a high specific surface area, and nitrogen is doped on the surface of the hollow core-shell material. Due to the nitrogen doping, the interplanar spacing is enlarged, making it easier for sodium ions with a larger ionic radius to be embedded and de-embedded in the interlayer spacing. Therefore, it can take into account the performance requirements required for efficient energy storage and further improve its electrochemical performance.

[0030] 3) On the one hand, the core-shell structure can give full play to the advantages of porous carbon derived from the two MOF materials, combining the conductivity of graphitized carbon and the high specific surface area of ​​porous carbon, contributing to a higher specific capacity; on the other hand, the double-layer hollow structure can shorten the ion transmission path and alleviate the volume strain during the charging and discharging process.

[0031] 4) The preparation method of the double-layer hollow core-shell structure porous carbon hybrid material prepared by the present invention is simple and easy to operate, safe and pollution-free, and low in cost.

[0032] 5) The double-layer hollow core-shell structured porous carbon hybrid material prepared by the present invention further enriches the types of MOF structural materials, expands the application field of MOFs materials, and provides more optional electrode active materials for high-efficiency electrochemical energy storage applications, which has great practical utilization value. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The left picture in the middle is a FESEM picture of the double-layer hollow Co-MOF-74 prepared in Example 1 of the present invention, and the right picture is a TEM picture of the double-layer hollow Co-MOF-74 prepared in Example 1 of the present invention;

[0034] Figure 2 The left figure is a FESEM image of the hollow core-shell structure of the double-layer Co-MOF-74@ZIF-8 prepared in Example 2 of the present invention, and the right figure is a TEM image of the hollow core-shell structure of the double-layer Co-MOF-74@ZIF-8 prepared in Example 2 of the present invention;

[0035] Figure 3 The left figure is a FESEM image of a double-layer hollow core-shell structure porous carbon hybrid material prepared in Example 2 of the present invention, and the right figure is a TEM image of a double-layer hollow core-shell structure porous carbon hybrid material prepared in Example 2 of the present invention;

[0036] Figure 4 a, b, and c are the XRD patterns of ZIF-8, double-layer Co-MOF-74, and double-layer hollow Co-MOF-74@ZIF-8 materials, respectively;

[0037] Figure 5 This is a diagram of the electrochemical performance of the sodium ion battery prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Example 1

[0040] The preparation method of double-layer hollow Co-MOF-74 powder comprises the following steps:

[0041] (1) 50 mg of 2,5-dihydroxyterephthalic acid and 50 mg of ZIF-67 were added to 150 ml of DMF and ultrasonicated for 20 min to form a solution. The solution was then transferred into a high-pressure reactor and placed in an oven at 110 °C for 750 min.

[0042] (2) The product was centrifuged, washed with ethanol, and dried in an oven at 80° C. to obtain a double-layer hollow Co-MOF-74 powder.

[0043] Figure 1 This is a FESEM image of the double-layer hollow Co-MOF-74 prepared in this example, which shows that the hexahedrons are evenly distributed and the surface is relatively smooth.

[0044] Example 2

[0045] The preparation method of the double-layer hollow Co-MOF-74@ZIF-8 core-shell structure porous carbon hybrid material comprises the following steps:

[0046] (1) 1 g of 2-methylimidazole was dissolved in 25 ml of methanol, and then 0.1 g of hollow Co-MOF-74 powder was added to form a uniform suspension A, which was stirred at room temperature of 25°C; 0.1 g of zinc nitrate hexahydrate was dissolved in 5 ml of methanol to form a solution B; the solution B was slowly added to the suspension A, stirred at room temperature of 25°C, and the reaction was stirred for 30 minutes;

[0047] (2) The product was centrifuged, washed with ethanol, and then dried in an oven at 80° C. for 12 h to obtain a double-layer hollow Co-MOF-74@ZIF-8 core-shell structure material;

[0048] (3) The double-layer hollow Co-MOF-74@ZIF-8 core-shell structure material was annealed at 800°C in argon, kept warm for 2 h, pickled in a nitric acid solution (the volume ratio of concentrated nitric acid to water in the nitric acid solution was 1:2), stirred in an 80°C water bath for 24 h, the product was centrifuged, washed three times with ethanol, and then placed in an oven at 80°C for 12 h to obtain a double-layer hollow core-shell structure porous carbon hybrid material.

[0049] Figure 2 FESEM and TEM images of the double-layer hollow Co-MOF-74@ZIF-8 core-shell structure prepared in this example. Figure 3The FESEM and TEM images of the double-layer hollow core-shell structured porous carbon hybrid material prepared in this example show that a uniform layer of ZIF-8 is successfully loaded on the original hexahedral surface, and many holes are formed after annealing. Figure 4 The XRD pattern of the double-layer hollow Co-MOF-74@ZIF-8 prepared in this example, the corresponding 2θ corresponds to the peak of the double-layer hollow Co-MOF-74, and also corresponds to the standard peak position of ZIF-8 reported in the literature, indicating that the hollow core-shell structure material was successfully prepared.

[0050] Example 3

[0051] A method for preparing a sodium ion battery comprises the following steps:

[0052] (1) The double-layer hollow core-shell structure porous carbon hybrid material prepared in Example 2 was uniformly mixed with conductive carbon black and PVDF in a mass ratio of 8:1:1 and dissolved in 1-methyl-2-pyrrolidone (NMP) to prepare a slurry, which was then uniformly coated on a copper foil current collector and dried in a vacuum drying oven at 60° C. for 24 h;

[0053] (2) The dried copper foil current collector was sliced ​​into negative electrode material, i.e., working electrode, with sodium metal sheet as positive electrode material, glass fiber as separator, and binary electrolyte. The 2032 button cell was assembled in an argon-filled glove box, and the test voltage range was 0.01V-3VvsNa + / Na.

[0054] Figure 5 This is a performance diagram of sodium electrochemical storage of sodium ions in the double-layer hollow core-shell structure porous carbon hybrid material prepared in Example 3. It can be seen that the sodium electrical performance of the double-layer hollow core-shell structure porous carbon hybrid material is relatively excellent.

[0055] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the present invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a double-layer hollow core-shell structure porous carbon hybrid material, characterized in that: The following steps are involved: S1. Dissolve 2-methylimidazole powder in methanol, then add double-layer hollow Co-MOF-74 powder to form a uniform suspension A, and stir at room temperature; The preparation method of double-layer hollow Co-MOF-74 powder includes the following steps: S101, adding 2,5-dihydroxyterephthalic acid and ZIF-67 to N,N-dimethylformamide to form a solution by ultrasonication, then transferring the solution into a high-pressure reactor and placing it in an oven for reaction, wherein the mass ratio of 2,5-dihydroxyterephthalic acid:ZIF-67 is 1:1, the ultrasonication time is 0-30 min, the oven temperature is 80-150 °C, and the reaction time is 30-1440 min; S102, centrifugally separating the product obtained in step S101, washing it with ethanol, and drying it in an oven to obtain a double-layer hollow Co-MOF-74 powder, wherein the oven temperature is 25-100 ° C, and the drying time is 30-720 min; S2, dissolving zinc nitrate hexahydrate in methanol to form solution B; S3, slowly adding solution B to suspension A, stirring continuously at room temperature, centrifuging the product, washing with ethanol, and drying in an oven to obtain a double-layer hollow Co-MOF-74@ZIF-8 core-shell structure powder; S4, the double-layer hollow Co-MOF-74@ZIF-8 core-shell structure powder was annealed under argon protection to obtain a double-layer hollow core-shell structure porous carbon hybrid material; S5. Place the double-layer hollow core-shell structure porous carbon hybrid material in a nitric acid solution, stir the reaction in a water bath, centrifuge the product, wash it with ethanol, and dry it in an oven to obtain a pure double-layer hollow core-shell structure porous carbon hybrid material.

2. The method for preparing a double-layer hollow core-shell structure porous carbon hybrid material according to claim 1, characterized in that: In the step S1, the concentration of 2-methylimidazole in the suspension A is 0.1-2 mol / L, the concentration of the double-layer hollow Co-MOF-74 is 1-5 g / L, and the room temperature is 25°C; In step S2, the concentration of solution B is 0.1 to 1 mol / L; In step S3, the room temperature is 25°C, the stirring time is 1 to 60 min, the oven temperature is 25-100°C, and the drying time is 30-720 min; In step S4, the annealing temperature is 600-900°C, and the holding time is 1-10 h; In step S5, the volume ratio of concentrated nitric acid to water in the nitric acid solution is 1:2, the water bath temperature is 25-90°C, the water bath time is 1-48 h, the oven temperature is 25-100°C, and the drying time is 30-720 min.

3. A double-layer hollow core-shell structure porous carbon hybrid material prepared according to the preparation method of the double-layer hollow core-shell structure porous carbon hybrid material according to any one of claims 1 to 2.

4. A negative electrode material for a sodium ion battery, characterized in that: The negative electrode material is prepared using the double-layer hollow core-shell structure porous carbon hybrid material described in claim 3.

5. A method for preparing a negative electrode material for a sodium ion battery, characterized in that: The following steps are involved: S1. The double-layer hollow core-shell structure porous carbon hybrid material according to claim 3 is uniformly mixed with conductive carbon black and polyvinylidene fluoride and dissolved in 1-methyl-2-pyrrolidone to prepare a slurry, which is then uniformly coated on a copper foil current collector and placed in a vacuum drying oven for drying; S2. Slice the dried copper foil current collector to make negative electrode materials for sodium ion batteries.

6. The method for preparing a negative electrode material for a sodium ion battery according to claim 5, characterized in that: In the step S1, the double-layer hollow core-shell structure porous carbon hybrid material, conductive carbon black, and polyvinylidene fluoride are in a mass ratio of 8:1:1, 1-methyl-2-pyrrolidone is 350 μl, the drying temperature is 25-100° C., and the drying time is 30-720 min.

7. A method for preparing a sodium ion battery, characterized in that: The following steps are involved: The negative electrode material of the sodium ion battery described in claim 4 is used as a working electrode, the glass fiber is used as a diaphragm, and the electrolyte is a binary electrolyte. The assembly is carried out in a glove box filled with argon gas to obtain the sodium ion battery.

8. The method for preparing a sodium ion battery according to claim 7, characterized in that: The electrolyte is sodium trifluoromethanesulfonate, the size of the working electrode is 12 mm, and the positive electrode material of the sodium ion battery is a metallic sodium sheet.

Citation Information

Patent Citations

  • Preparation method and application of one-dimensional core-shell structure porous carbon

    CN111916737A

  • Reduced graphene oxide-based hollow Co-MOF composite flexible electrode material and preparation method thereof

    CN113921778A